The Milky Way smells of rum and raspberries : ...and other amazing cosmic facts - Scudder, Jillian (Icon Books, 2022)
Astrophysicist Dr Jillian Scudder knows more than most of us what a surreal place the Universe can be. In this light-hearted book she delves into some of the more arcane facts that her work has revealed, and tells us how we have actually managed to discover these amazing truths.